Apoptosis-mediated anti-proliferative activity of Calligonum comosum against human breast cancer cells, and molecular docking of its major polyphenolics to Caspase-3 - Kumar, Ashok; Alfhili, Mohammad A.; Bari, Ahmed; Ennaji, Hanane; Ahamed, Maqusood; Bourhia, Mohammed; Chebaibi, Mohamed; Benbacer, Laila; Ghneim, Hazem K.; Abudawood, Manal; Alghamdi, Khalid M.; Giesy, John P.; et al. (Frontiers in Cell and Developmental Biology, 2022)
Due to poor diagnosis breast cancer in women has emerged as the most common cause of death disease in developing countries. Medicinal plants have been used for thousands of years and can be useful in healthcare, especially in developing countries. Ethanol extracts of leaves of fire bush or arta (Calligonum comosum; EECC), exhibited significant anticancer potencies against two breast cancer cells, MCF-7 and MDA 231. These in vitro effects of EECC indicated potential anticancer activities that were determined to be specific since minimal toxicity was recorded against MCF-12, a non-cancerous breast cell line used as a control. EECC also induced cell cycle arrest in MCF-7 and MDA 231 as revealed by the increased proportions of sub-G1 cells. Fluorescence-activated cell sorter analysis (FACS), utilizing double staining by annexin V-FITC/propidium iodide, revealed that the obtained cytotoxic activity was signaled through apoptosis and necrosis. FACS measurement of the elevation in fluorescence intensity linked with DCFH oxidation to DCF revealed that apoptosis is attributed to the production of free radicals. EECC-mediated apoptosis was further validated by observation of up-regulation in the “executioner” enzyme, caspase 3. The current findings reveal that EECC exhibits significant, selective cytotoxicity to breast cancer cells, that proceeds via the generation of ROS, which culminates in apoptosis. The antiproliferative effect of EECC was further verified by use of a structure-based, virtual screening between its major bioactive polyphenolic constituents and the apoptosis executioner marker enzyme caspase-3. Based on their glide score values against caspase 3 active site, some phytoconstituents present in EECC, namely DL-alpha-tocopherol followed by campesterol, showed distinctive drug-like potential with no predicted toxicity to non-target cells. Taken together, the usefulness of natural phenolic and flavonoid compounds contained in C. comosum were predicted to be potent anticancer agents.